A solid support generator of the Auger electron emitter rhodium-103m from [103Pd]palladium. (February 2020) - Jensen, Andreas I.; Zhuravlev, Fedor; Severin, Gregory; Magnus, Charlotte Busk; Fonslet, Jesper; Köster, Ulli; Jensen, Mikael
Abstract: Auger electron therapy is an attractive modality for targeting microscopic tumors. Rhodium-103 m ( 103m Rh, T½  = 56.1 min) is a promising Auger electron emitter that can be obtained as the decay product of palladium-103 ( 103 Pd, T½  = 16.99 days). 103 Pd was chelated in a lipophilic derivative of the 16aneS4 macrocycle and the complex was trapped on a C18 cartridge. Elution with dilute hydrochloric acid gave radiochemically pure 103m Rh. We hypothesize this to be through a combination of the Szilard-Chalmers effect and transient ionization. Highlights: [ 103 Pd]PdCl2 was obtained by dissolving neutron irradiated 102 Pd-enriched targets. [ 103 Pd]Pd was chelated by a 16aneS4-octyl derivative and trapped on a C18 support. Elution of this generator provided 103m Rh in excellent radiochemical purity. The demonstrated generator will allow investigating 103m Rh for Auger radiotherapy.